Hypercalcemia in pregnancy due to CYP24A1 mutations: case report and review of the literature - Pilz, Stefan; Theiler-Schwetz, Verena; Pludowski, Pawel; Zelzer, Sieglinde; Meinitzer, Andreas; Karras, Spyridon N.; Misiorowski, Waldemar; Zittermann, Armin; März, Winfried; Trummer, Christian (Nutrients, 2022)
Pathogenic mutations of CYP24A1 lead to an impaired catabolism of vitamin D metabolites and should be considered in the differential diagnosis of hypercalcemia with low parathyroid hormone concentrations. Diagnosis is based on a reduced 24,25-dihydroxyvitamin D to 25-hydroxyvitamin D ratio and confirmed by genetic analyses. Pregnancy is associated with an upregulation of the active vitamin D hormone calcitriol and may thus particularly trigger hypercalcemia in affected patients. We present a case report and a narrative review of pregnant women with CYP24A1 mutations (13 women with 29 pregnancies) outlining the laboratory and clinical characteristics during pregnancy and postpartum and the applied treatment approaches. In general, pregnancy triggered hypercalcemia in the affected women and obstetric complications were frequently reported. Conclusions on drugs to treat hypercalcemia during pregnancy are extremely limited and do not show clear evidence of efficacy. Strictly avoiding vitamin D supplementation seems to be effective in preventing or reducing the degree of hypercalcemia. Our case of a 24-year-old woman who presented with hypercalcemia in the 24th gestational week delivered a healthy baby and hypercalcemia resolved while breastfeeding. Pathogenic mutations of CYP24A1 mutations are rare but should be considered in the context of vitamin D supplementation during pregnancy.
Gesehen am 06.02.2024
Dieser Artikel gehört zum Special issue: COVID-19 and other pleiotropic actions of Vitamin D